Estratégias para melhorar a eficiencia da seleção em progênies de meios irmãos por meio de simulação - Fernandes, Samuel Bonfim (2016)
Plant breeding provides several alternatives for obtaining superior cultivars. When the goal is to improve the performance of a population, the strategies used may involve the selection of either individuals or progenies. In this case, half-sib progenies are often preferred, especially for being easy to work with. In this context, we performed this study to evaluate, through computer simulation, strategies that help in the decision-making regarding to the number of progenies, repetitions and plants per plot to increase effectiveness in breeding programs that uses half-sib progenies. Experiments with half-sib progenies were simulated considering a trait controlled by 100 genes, varying the average degree of dominance (0 or 1), the mean allelic frequency of the population (0;2, 0;5 or 0;8) and heritability (0;1, 0;25 or 0;5). It was considered a breeding program with the ability to assess 6:000 plants in experiments with multiple plants or single plant plot. In the first case, we used N f progenies, with N f ranging between 60 and 600, in 2, 3, 4 or 5 repetitions with k plants/plot (5, 10 or 20). Recombination occurred with and without the use of remaining seeds, with selection within progenies only in the maternal side. In the case of one plant per plot, N f ranged between 12 and 600 progenies, with 500 and 10 repetitions, respectively. It was considered in this case, the selection among and within progenies in both sexes. The results of this study shows that increasing the number of repetitions over the number of plants per plot, provides larger genetic gain. The gains were, on average, higher in experiments with single plant plot. It also shows that it is possible to obtain similar genetic gain with different number of progenies. However, the results obtained with the use of fewer progeny shows large fluctuations and therefore greater risks. On other hand, the use of fewer plants per progeny, on average, result in lower gain. For the situations considered in this study, the use of about 100 progenies in 60 repetitions resulted in a better ratio between the magnitude of genetic gains and the accuracy of the estimates.